Postpartum depression among women with pre-eclampsia and eclampsia in Tanzania; a call for integrative intervention - Barke Mbarak; Charles Kilewo; Saidi Kuganda; Bruno F. Sunguya (BMC, 2019)
Abstract Background Postpartum depression (PPD) complicates maternal wellbeing, maternal-infant bonding, and cognitive function in children and woman's relationship with her partner. Clinical observations suggest a higher risk of postpartum depression among those women with pre-eclampsia and eclampsia compared to the general population. However, the evidence is inconsistent and not from settings similar to Tanzanian. This study aimed to determine the magnitude and risk factors for PPD among women diagnosed with pre-eclampsia or eclampsia at Muhimbili National Hospital (MNH), Tanzania. Methods This cross-sectional study was conducted among 390 women who had pre-eclampsia or eclampsia during pregnancy attending postnatal care clinic at MNH. PPD was assessed using Edinburg postnatal depression scoring scale (EPDS). Face to face interviews was conducted and data was analysed using descriptive and logistic regression analysis to address the two respective objectives. Results PPD was prevalent among 20.5% of women who had pre-eclampsia or eclampsia but varied with severity. Factors associated with PPD included young age (AOR = 10.13 95% CI 1.99-52.02), being a single mother (AOR = 3.18 95% CI 1.02-9.95), having a lower level of education (AOR = 3.83 95% CI 1.45-10.16), having a perinatal death (AOR = 5.14 95% CI 2.53-10.45), lack of family support (AOR = 7.06 95% CI 1.25-39.90), and experience of stressful event during pregnancy (AOR = 15.14 95% CI 2.38-96.19). Conclusion One in five women with pre-eclampsia or eclampsia had PPD and the magnitude increased with the severity of the disease condition. To address PPD, efforts should be done to screen and provide treatment to pregnant women presenting with pre-eclampsia or eclampsia, especially those with young age, low education level, single marital status, perinatal loss, lack of family support, and those reported to have a stressful event during pregnancy.